2008
DOI: 10.1007/s10342-008-0232-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity blurs ecotypic divergence in the response of Quercus coccifera and Pinus halepensis to water stress

Abstract: The Mediterranean evergreen woody plants Quercus coccifera and Pinus halepensis grow in a range of environments where selection by drought, heat and high irradiance can drive genetic and phenotypic diVerentiation of populations. However, the role of these stresses in Wltering out maladaptive genotypes remains unknown. We hypothesize that this Wltering is an important process for woody Mediterranean species due to their low phenotypic plasticity reported in previous studies. We have studied the response of sapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 51 publications
(82 reference statements)
10
50
1
1
Order By: Relevance
“…Regarding phenotypic plasticity, and according to RDPI range established by Valladares et al (2006), the tested Salzmann pine seed sources showed low phenotypic plasticity for both growth traits and survival, which concords with previous results of pine species such as Pinus halepensis (Baquedano et al, 2008) or on other Mediterranean species such as Quercus coccifera (Balaguer et al, 2001), Quercus robur and Fagus sylvatica (Valladares et al, 2000(Valladares et al, , 2002. Some traits might vary in their sensitivity to the environment being more plastic than others (Aitken et al, 2008;Benito-GarzĂłn et al, 2011) as was the case in our experiment where height growth plasticity was higher than of that diameter among sites.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Regarding phenotypic plasticity, and according to RDPI range established by Valladares et al (2006), the tested Salzmann pine seed sources showed low phenotypic plasticity for both growth traits and survival, which concords with previous results of pine species such as Pinus halepensis (Baquedano et al, 2008) or on other Mediterranean species such as Quercus coccifera (Balaguer et al, 2001), Quercus robur and Fagus sylvatica (Valladares et al, 2000(Valladares et al, , 2002. Some traits might vary in their sensitivity to the environment being more plastic than others (Aitken et al, 2008;Benito-GarzĂłn et al, 2011) as was the case in our experiment where height growth plasticity was higher than of that diameter among sites.…”
Section: Discussionsupporting
confidence: 67%
“…Height differed more among seed sources than diameter growth within each site. This can be explained by the fact that seedlings diameter, being frequently more sensitive to change in environmental conditions, is further fixed than height in establishing seedlings (Baquedano et al, 2008). However, there were specific differences among sites, with height growth being higher in Berga while in Xert diameter growth was the highest and height growth rates were the lowest.…”
Section: Discussionmentioning
confidence: 78%
“…Similar observations have been made in semiarid regions of Turkey, Algeria and Morocco (BarbĂ©ro et al 1998;Pausas et al 2004). From a functional point of view, Pinus halepensis is considered not only a droughtavoider isohydric species with efficient stomatal control over water use (Baquedano et al 2008), but also a species that displays moderate resistance to the xylem embolism compared to other Pinus sp (Choat et al 2012).…”
Section: Introductionmentioning
confidence: 55%
“…Such ecotype differentiation may be due to the long-term selection pressure that caused these populations to adapt to local environmental and edaphic conditions (Kawecki & Ebert 2004;Savolainen et al 2007). Such development of ecotypes due to the adaptational pressures of local climate and soil is also reported in other species such as Pinus taeda L. (Bongarten & Teskey 1986), Picea abies L. (Oleksyn 1998), Pinus sylvestris L. (Palmroth 1999), Fagus sylvatica L. (MĂŒller-Stark 1997;Peuke 2002) and Quercus coccifera L. (Baquedano 2008). Soolanayakanahally et al (2009) found that species growing in wide geographical ranges showed great potential to acquire larger intraspecific variation in physiology, phenology, morphology and growth rate, which are clearly visible in case of these growth forms of D. strictus growing in different geographical locations.…”
Section: Rapd Banding Patternmentioning
confidence: 98%